Upaya Meningkatkan Hasil Belajar Siswa pada Materi Dinasti Abbasiyah melalui Model Problem Based Learning - Purnamasari, Rita (Edu Berkah Khatulistiwa, 2025)
This study aims to improve the quality of students' learning outcomes in the Abbasid Dynasty material through the application of the Problem Based Learning (PBL) learning model in class VIII MTs Nurusshibyan Singkawang. This research adopts the Classroom Action Research (CAR) method which is carried out in two cycles, where each cycle includes the stages of planning, implementation, observation, and reflection. Data collection was carried out using learning outcome evaluation tests, observations of student activities, and documentation during the learning process. The research findings show a significant increase in students' academic achievement after the PBL model was applied. In the first cycle, the student completion rate reached 76%, then increased to 87% in the second cycle. In addition, there was significant development in student activity and involvement when participating in learning activities. Based on these data, it can be concluded that the Problem Based Learning model is effective in improving student learning outcomes in learning the Abbasid Dynasty material. Thus, this study recommends the application of PBL as an innovative alternative to increase the effectiveness of learning Islamic Cultural History.